Strongly carinate species of Alpheopsis Coutière, 1897 of the tropical Atlantic and eastern Pacific, with redescription of A. trigona (Rathbun, 1901) and description of three new species (Malacostraca: Decapoda: Alpheidae) - Anker, Arthur (Zootaxa, 2017)
The present study deals with four species of the alpheid shrimp genus Alpheopsis Coutière, 1897 characterised by the presence of at least one strong carina on the dorsal surface of the carapace. Alpheopsis trigona (Rathbun, 1901) is redescribed based on the holotype from Puerto Rico and additional material from US Virgin Islands and Florida. Two new species closely related to A. trigona, viz. A. paratrigona sp. nov. and A. gotrina sp. nov., are described, the first based on material from several localities in the tropical western Atlantic, and the second from the Pacific coast of Panama and Colombia. The three species together form a distinctive transisthmian clade within Alpheopsis, the A. trigona species complex, characterised by the presence of several strong longitudinal carinae on the carapace and very distinctive colour pattern. A more distantly related species, A. aristoteles sp. nov., characterised by the presence of only one strong mid-dorsal carina in the anterior region of the carapace, is described based on material from São Tomé Island in the tropical eastern Atlantic.